2022
DOI: 10.3389/fendo.2022.808298
|View full text |Cite
|
Sign up to set email alerts
|

TERT Promoter Mutations Are an Independent Predictor of Distant Metastasis in Middle Eastern Papillary Thyroid Microcarcinoma

Abstract: BackgroundPapillary thyroid microcarcinomas (PTMCs) have been attributed to the recent increased incidence of thyroid cancer. Although indolent, a subset of PTMC could potentially develop distant metastasis (DM). This study aimed to evaluate the clinico-pathological features and molecular characteristics of PTMC and identify the risk factors for DM in PTMC patients from Middle Eastern ethnicity.MethodsWe retrospectively analyzed 210 patients with histologically confirmed PTMC. Clinico-pathological associations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…The incidence of PTC is higher in Saudi Arabia compared to Western populations and it ranks as the second most common malignancy among females in this ethnicity, accounting for 14.3% of all cancers [ 4 ]. Further, as reported by this study and in other studies on Middle Eastern populations, the incidence of recurrence (18.4%) [ 27 ], lymph node metastasis (53.0%) [ 28 ], and distant metastasis (7.5%) [ 29 ] is higher compared to other ethnicities. Another important difference is the earlier age of onset for PTC in Middle Eastern populations.…”
Section: Introductionsupporting
confidence: 85%
“…The incidence of PTC is higher in Saudi Arabia compared to Western populations and it ranks as the second most common malignancy among females in this ethnicity, accounting for 14.3% of all cancers [ 4 ]. Further, as reported by this study and in other studies on Middle Eastern populations, the incidence of recurrence (18.4%) [ 27 ], lymph node metastasis (53.0%) [ 28 ], and distant metastasis (7.5%) [ 29 ] is higher compared to other ethnicities. Another important difference is the earlier age of onset for PTC in Middle Eastern populations.…”
Section: Introductionsupporting
confidence: 85%
“…2 b), which was consistent with the finding of a previous study that also compared the mutation rates between China and TCGA (72.4% & 59.7%) [ 12 ]. Parvathareddy et al showed BRAF V600E mutations were detected in 45.7% (84/184) Middle Eastern PTMCs, which was less than the PTMETA cohort [ 58 ]. Iodine-rich diets or chronic thyroiditis were suspected to be possible reasons for high BRAF V600E mutations in Chinese PTC [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although BRAF mutation had been associated with lymph node metastases, extrathyroidal extension, tumor size, and advanced disease stage [16], more recent studies have questioned its impact on risk stratification and prognosis for PTC [17]. However, TERT promoter mutation has been found to be an independent predictor of distant metastasis, recurrence, and disease-free survival [18][19][20][21]. Moreover, its copresence with BRAF mutation has been associated with even more aggressive clinicopathological characteristics [22].…”
Section: Discussionmentioning
confidence: 99%